The Contribution of Digital Transformation, Innovation and Technology Adoption To Business Opportunities For Msmes In Serang City - Icin Quraysin; Siti Muawanah; Adelawinda Iryana; Asep Chandra; Opan Baehaqi; Riski Wulandari (CV. Inara, 2026)
This study aims to analyze the contribution of digital transformation, innovation, and technology adoption to business opportunities for MSMEs in Serang City. The development of the digital economy requires MSMEs to be able to adapt through the use of technology, increase business creativity, and continuous innovation in order to be able to compete and grow. The research method used is a quantitative approach with a questionnaire technique for data collection to 120 MSMEs in Serang City selected using purposive sampling. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results show that digital transformation partially has a positive and significant effect on business opportunities, innovation has a positive and significant effect on business opportunities, and technology adoption has a positive and significant effect on business opportunities. Simultaneously, digital transformation, innovation, and technology adoption have a significant effect on MSME business opportunities in Serang City with a coefficient of determination of 61.2%. This indicates that MSME business opportunities are strongly influenced by the ability to utilize digital technology, create innovation, and adopt new technologies in business operations. This study implies that increasing digital literacy, strengthening innovation, and technological support need to be continuously developed to encourage the competitiveness and sustainability of MSMEs in the digital economy era.